The Influence of Debt Policy, Profitability and Company Size on Company Value in Consumer Goods Sector Companies Listed on the Indonesia Stock Exchange (BEI) for the 2019 - 2022 Period - Marsaoly, Novita Romla (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to examine the influence of debt policy, profitability and debt policy on company value in consumer goods sector companies listed on the IDX for the 2019 - 2022 period. Debt policy is measured by the debt equity ratio DER, profitability is measured by Return On Assets (ROA) , natural logarithm (Ln). The population in this study is all companies in the consumer goods sector listed on the Indonesia Stock Exchange (BEI), a total of 47 companies. The sampling technique used was Porposive Sampling and 18 companies were obtained with a research period of 4 years, thus obtaining 70 sample data. This research method used SPSS version 25 with the data analysis techniques used were the classical assumption test, multicollinearity, heteroscedasticity, normality test, coefficient test m correlation and determination, simultaneous test and partial test. The research results show that debt policy, profitability and company size simultaneously have a significant effect on company value.